PERLINDUNGAN HUKUM ATAS JUAL BELI HAK ATAS TANAH YANG BELUM BERSERTIPIKAT - Aris Yulia; Fatma Ayu Jati Putri (Journal of Innovation Research and Knowledge, 2024)
This writing is useful in examining the process of buying and selling rights to land that has not been certified and the legal protection provided in this context. Apart from that, this writing also focuses on legal protection of the rights of the parties involved in the transfer of land rights. Documentation of land ownership is very important in land transactions, such as buying and selling, because these rights must be transferred to official ownership status after the land buying and selling transaction is completed. So that land ownership can be clearly determined after the sale and acquisition of land. Normative legal research is the methodology used in this research. Research data comes from previous laws as well as literature from various statutory regulations. Qualitative analysis is used for each data analysis. According to research findings, protection of legal land sales and purchases is necessary because, automatically, ownership rights are transferred upon completion of a legal transaction. The findings of this research establish legal certainty for the parties involved and the preservation of a person's right to control their land rights by protecting the sale and purchase of land